The influence of hydrogenation on superconducting properties of MgB₂ - Zaleski, A.J.; Iwasieczko, W.; Kaczorowski, D.; Drulis, H.; Tkacz, M.; Klamut, J.; Zogal, O.J. (Физика низких температур, 2001)
In the paper we present the results of the ac susceptibility measurements of two

newly discovered superconducting diboride - MgB₂.